Interfacial Activity of Metal beta-Diketonato Complexes: In Situ Generation of Amphiphiles by Water Coordination - Vogel, Nicolas; et al. (Langmuir, 2011)
Symmetric transition metal complexes of 2,4-pentanedione (acetyl acetone) are interfacially active: Spinning drop tensiometry reveals lowering of the interfacial tension at the water-organic interface, most pronounced for [Cr(acac)(3)], [Fe(acac)(3)], [Zr(acac)(4)], and [Hf(acac)(4)]. The interfacial activity is explained by the in situ generation of amphiphilic species. Based on tensiometry and (1)H and diffusion-ordered NMR spectroscopy (DOSY NMR), hydrogen bonding of the organically dissolved complexes with water, in some cases in combination with inner-sphere hydrolytic coordination, is identified as the primary origin of this amphiphilicity. The complexes are a rare example of symmetric molecules that turn amphiphilic only upon interfacial interaction with water.